UNDERSTANDING VARIOUS RESEARCH TOOLS TO INVESTIGATE PRONUNCIATION ERRORS OBSERVED AMONG INDONESIAN EFL LEARNERS: SOME THEORETICAL NOTES TO ATTEND - Darwanto, Agus; Herusatoto, Hesthi (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2024)
This article is about the main theoretical framework adopted in the analysis of, especially, pronunciation errors. Such theories as Contrastive Analysis Hypothesis, Error Analysis, Language Universals, and Markedness Differential Hypothesis, all of which are interlingual suggest that interlingual differences as well as similarities create pronunciation problems. In this work, several types of errors as postulated by many scholars are presented to intricate with the theories being discussed. Note that first, according to the scholars, not all points of difference between the linguistic structures of L 1 (first language) and L2 (second language) create the same extent of errors. Divergent contrasts (dissimilarities) seem to be more readily acquired than convergent contrasts (similarities). Contrastive analyses are of two versions, strong and weak. Second, in general, cross-linguistic differences, regardless of the error type, should not necessarily hinder learning as long as enough explicit instruction and sufficient exposure to target-like pronunciation are provided.